A comprehensive study of dielectric, modulus, impedance, and conductivity of SrCeO3 synthesized by the combustion method - Verma H.; Tripathi A.; Upadhyay S. (My University, 2025)
In this work, perovskite oxide SrCeO3 was synthesized using the solution combustion method (SCM). Synthesized samples have been characterized using X-ray diffraction (XRD), Raman, ultra violet (UV)–visible spectroscopy, and scanning electron microscopy (SEM) techniques. The XRD and Rietveld refinement has confirmed the orthorhombic structure with space group Pnma. The average grain size of this ceramic sample is 1.2 µm. The dielectric constant, dissipation factor, modulus, impedance, and alternating current (AC) and direct current (DC) conductivities were analyzed in the temperature range RT to 600°C and frequency range 20 Hz–2 MHz. Further, it was observed that the role of grain boundaries in dielectric and electrical properties is significant, at low temperatures. The origin of the dielectric relaxation and conduction process is the same. The activation energy for DC conduction (Edc) was found to be.79 eV. Electrical conduction/relaxation is assigned to the diffusion of doubly ionized oxygen (Vo··). The value of DC conductivity (1.2 × 10−3 Ω−1 cm−1 at 600°C) and activation energy of.79 eV is very close to the values reported for doped CeO2-based oxide ion conductors for SOFCs. This study has demonstrated that SrCeO3 can be an alternative candidate for the oxide ion conductor electrolyte application and the potential to be used as a thermally stable capacitor application for microwave dielectric applications. © 2024 The American Ceramic Society.